Regulatory Framework of the Conduct of Forensic Construction Examination - A. A. Revunov (Теория и практика судебной экспертизы)
This article addresses the pressing issue of reforming the system of regulation for construction activities. The author analyzes the advantages and disadvantages of the existing opposing points of view: preserving the existing “rigid” system on the one hand, or its abolition – the transition to the “flexible” method of calculation justification of design decisions, on the other. The choice in favor of the second option will cause large-scale changes in the construction sector, hence – forensic construction activities. Such changes will undermine the entire forensic expertise institution because it will become impossible to comply with the basic principles of an expert’s work - scientific validity and reliability of conclusions. The author concludes that the current regulating system does not work not because of its shortcomings but for some other reasons: negligence in construction work conduct, non-compliance with the construction technology, lack of design documentation, and others. In order to improve the current situation concerning the regulation of forensic construction and technical examinations, the following measures have been proposed: revision and improvement of their methodological, theoretical, and legal foundations, in-depth analysis of the content of urban planning legislation from the point of view of requirements mandatory for application by a forensic expertbuilder, specifying the limits of an expert’s competence, the formation of unified algorithms and forms of presenting research, the development of sub-theories on the legal and organizational support of the nonstate forensic activity, the active involvement of research institutions and higher educational institutions in the conduct of expert examinations.